ЭФФЕКТИВНОСТЬ ИСПОЛЬЗОВАНИЯ ВИТАМИНА D В ЛЕЧЕНИИ ДЕТЕЙ С АЛЛЕРГИЕЙ К БЕЛКАМ КОРОВЬЕГО МОЛОКА - Налетов, А. В.; Шапченко, Т. И.; Коктышев, И. В. (Университетская клиника, 2019)
The article presents the results of a study on the level of vitamin D in children of first year with cow's milk proteins allergy. The aim of the work is to evaluate the effectiveness of using an aqueous solution of vitamin D in addition to a therapeutic elimination diet in children who are allergic to cow's milk proteins. It was found that the 57.1±4.8 % children of first year with cow's milk proteins allergy have vitamin D insufficiency. Normal vitamin D levels were found in only 36.2±4.7 % % patients. In turn, vitamin D deficiency were found in 6,7±2,4 % children. The additional intake of vitamin D on the background of the use of elimination therapeutic dairy-free diet can reduce the time of development of tolerance to cow's milk proteins and achieve tolerance for three years in 92 % of children with allergies to cow's milk proteins were found.